PERANCANGAN SLIDE SHOW VIDEO BER-GENRE GLICT ART SEBAGAI MEDIA PROMOSI PRODI DKV IIB DARMAJAYA - Ade Moussadecq; Abdi Darmawan; Yan Aditya Pratama (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2023)
Promotion is an activity carried out by an entity to influence consumer behavior to try a product or service offered by that entity (A'lawiyyah et al., 2021). A promotional activity required media that can reach a wider audience. The use of Instagram media as the main media for promotional activities is certainly the right choice, taking into account the activities of modern humans at this time that are never separated from gadgets or smartphones. The use of video as an advertisement representation will certainly be very effective in today's digital era. The implementation of this research uses applied methods resulting from research to solve the problems of the IIB Darmajaya visual communication design study program. After obtaining research data, data analysis using the SWOT method is needed to assist in the preparation of marketing content and important components that have been neglected so far. The design method used in this research is pre-production, production, and post-production.Â